Pragmatic critical realism and Mixed methods in Inter-disciplinary Research—Management and Information systems (International Journal of Scientific Research and Management (IJSRM), 2024)
Mixed methods research traditionally follows one paradigm based on established typologies. However, this study deviates from conventional research paradigms by combining two paradigms in one study. Specifically, it employs a critical realist method to analyze data, complemented by a pragmatist approach. This combination allows for the exploration of various phenomena in multidisciplinary research, such as cyber risk management, which intersects with management and information systems. By delving into the causal mechanisms underlying observed social and organizational phenomena, the pragmatic critical realism (PCR) approach, in conjunction with mixed methods research (MMR), offers a valuable framework for understanding the study’s findings. Importantly, PCR has not been widely discussed or adopted in a multidisciplinary context for examining mixed data and advancing theory using MMR. This approach can be applied to multidisciplinary research in different contexts, enabling a deeper understanding of research participants’ perspectives, the observable events resulting from those perspectives, and their causal relationships. The study systematically reviews the literature on pragmatism and critical realism in the field of management and information system; compares and combines these two research paradigms to identify common ground and explore their potential for developing a new framework to address interdisciplinary research questions. As a result, a new multiparadigm conceptual model has been established that integrates pragmatism and critical realism, making an original contribution to the field of mixed methods research. The study suggests that academics and researchers in management and information systems should broaden their use of methodologies and embrace interdisciplinary thinking in order to advance theoretical debates within their discipline.